Tame the wild man - Koh, Yu Juan (2018)
With Singapore striving to be a city in a garden, the chances of interaction with our native animals increases. “Tame the Wild Man” is a project that aims to improve Human-Wildlife conflict in Singapore by researching and designing a strategy consisting of Education, Empathy, and Action. The project research moves from questioning the reason of conflict to how the general population can help facilitate the conflict. The project will focus on the creation of a series of educational illustrated book with 6-10 years old children as the target audience. The illustrated book aims to instill tolerance and empathy through the eyes of our wildlife—on acknowledging that the space we share is ours as much as it is theirs. This in turn strives towards altering our attitudes and behaviors in negotiating our city spaces.